Comparative Study of Promastigote- and Amastigote-Initiated Infection of Leishmania infantum (Kinetoplastida: Trypanosomatidae) in Phlebotomus perniciosus (Diptera: Psychodidae) Conducted in Different Biosafety Level Laboratories. Issue 2 (8th November 2019) - Vaselek, Slavica; Prudhomme, Jorian; Myskova, Jitka; Lestinova, Tereza; Spitzova, Tatiana; Bañuls, Anne-Laure; Volf, Petr
Abstract: Sand flies (Diptera: Psychodidae) are natural vectors of Leishmania . For the initiation of sand fly experimental infections either Leishmania amastigotes or promastigotes can be used. In order to obtain comparable results, it is necessary to adjust and standardize procedures. During this study, we conducted promastigote- and amastigote-initiated infections of Leishmania infantum Nicolle, 1908 parasites in Phlebotomus ( Larroussius ) perniciosus Newstead, 1911 in two laboratories with different levels of biosafety protection. Protocol originally designed for a biosafety level 2 facility was modified for biosafety level 3 facility and infection parameters were compared. Particularly, specially designed plastic containers were used for blood feeding; feeders were placed outside the sand fly cage, on the top of the mesh; feeding was performed inside the climatic chamber; separation of engorged females was done in Petri dishes kept on ice; engorged females were kept in the cardboard containers until dissection. All experiments, conducted in both laboratories, resulted in fully developed late stage infections with high number of parasites and colonization of the stomodeal valve. We demonstrated that protocol originally designed for biosafety level 2 facilities can be successfully modified for other biosafety facilities, depending on the special requirements of the individual institution/laboratory.